How gender affects the mental health of healthcare workers across regions in Thailand - Nattanicha Chairassamee; Kanokwan Chancharoenchai (BMC Health Services Research)
Abstract Background A shortage of healthcare professionals in Thailand can cause mental health impairment, low quality of life, high resignation rates, and low-quality services to patients due to heavy responsibilities. With the increasing rate of females entering medical careers, gender has become a significant factor in assessing healthcare workers’ mental health. This study explores the relationship between the mental health and gender of healthcare workers across geographic regions in Thailand. Methods The present study uses individual data of Thai healthcare workers from 2009 to 2015 and 2018—prior to the COVID-19 pandemic. We include overall mental health and work/job-related mental health. A linear regression with fixed effects is used to estimate the differentials of healthcare workers’ gender on mental health issues. Results Female healthcare workers feel more depressed and less satisfied with their health management than males do, particularly in rural areas. Young female healthcare professionals have lower levels of happiness and life satisfaction than male workers do. Predictions of mental health levels from our regressions show that nurses in rural areas experience higher levels of mental health impairment than doctors do. Conclusions Female workers are more likely to feel depressed than males are, particularly in rural areas. We also find that nurses are less likely to be happy and satisfied with life than doctors are.